Method for preparing ordered concentration-doped nanocrystalline coating through reversed-phase colloidal dispersion system
The preparation of ordered concentration-doped nanocrystal coatings through the reverse phase colloid dispersion system solves the problem of insufficient electrochemical performance and structural stability of nanocrystal coatings in the prior art, and achieves efficient preparation and orderly doping of nanocrystal precursors, improving the overall performance of the material.
Patent Information
- Application Number
- CN202411837532.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to effectively improve the electrochemical performance and structural stability of nanocrystal coatings through orderly doping, and it is difficult to achieve efficient preparation of nanocrystal precursors.
Through the reverse phase colloid dispersion system, an ordered concentration doped nanocrystal coating is prepared. The specific steps include the preparation of the matrix nanocrystal precursor reverse phase colloid and microwave maturation, combined with the combination of different organic acids and polymers to achieve the aggregation and order doping of the nanocrystal precursor.
The orderly doping of nanocrystal coatings is achieved, which improves the electrochemical performance and structural stability of the material, reduces capacity attenuation, and improves the overall performance.
Smart Images

Figure CN119552559A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of reversed-phase colloidal dispersion system, ordered doping and nanocrystalline coating, and in particular to a method for preparing ordered concentration-doped nanocrystalline coating by reversed-phase colloidal dispersion system. Background Art
[0002] Doping refers to the addition of a small amount of other elements or compounds to a material or matrix to improve its performance. This process is widely used in the fields of chemical industry, materials, etc., with the aim of obtaining specific electrical, magnetic and optical properties, thereby giving the material specific value or use. Doping ions enter the crystal lattice or the lattice gap to form doped crystals. After doping, holes can be formed without causing the crystal structure to collapse, because the lattice can withstand certain lattice distortions through the crystal. Ordered doping can optimize the performance of the material by introducing different concentrations of doping elements into the material to form an ordered concentration change. This method can reduce stress concentration caused by doping and improve the uniformity and stability of the material. Ordered doping can significantly improve the electrochemical properties and structural stability of the material, reduce capacity attenuation, and improve the overall performance of the material.
[0003] A system formed by a substance or several substances being highly dispersed in another substance is called a dispersed system. The dispersed substance is called a dispersed phase, and the continuous medium is called a continuous phase. According to the different states of existence of the dispersed phase and the continuous phase, if the dispersion medium is liquid, it is called a liquid dispersed system. This type of dispersed system is the most common and important in chemical reactions. Aqueous solutions, suspensions, and emulsions all belong to liquid dispersed systems. There is no absolute limit to the linear size (approximately the size of its diameter) of dispersed phase particles in solutions, suspensions, and emulsions. Generally speaking, when the one-dimensional size of the dispersed phase particles is less than 1-9nm, it is a solution. The particles in the solution are actually in the state of molecules, ions, or hydrated molecules and hydrated ions. The one-dimensional size of the dispersed phase particles is between 10-100nm, which is a colloid (some organic aqueous solutions, such as starch solutions, are actually colloids). A high-intensity homogenizer must be used when dispersing and preparing submicron fine emulsions. Commonly used ones are rotary shear type homogenizers, ultrasonic homogenizers, and high-pressure jet homogenizers. Coating is a solid continuous film obtained by applying paint. It is a thin layer of plastic applied to a substrate such as metal, fabric, plastic, etc. for the purpose of protection, insulation, decoration, etc. The paint can be gaseous, liquid, or solid. The type and state of the paint is usually determined by the substrate to be sprayed. Summary of the invention
[0004] The purpose of the present invention is to prepare an ordered doped nanocrystalline coating using an inverse colloid, and the specific method is carried out according to the following steps:
[0005] (1) Preparation of reverse colloid containing matrix nanocrystal precursor and microwave ripening of the precursor
[0006] At room temperature, a quantitative matrix metal salt aqueous solution and a quantitative polymer aqueous solution are mixed to form an aqueous phase; and an oil phase is formed by a quantitative mixed solvent. After the oil and water phases are mixed, they are quickly transferred to an ultrasonic pulverizer, pulverized at a certain temperature for a certain time according to a set method, and then an alkaline aqueous solution of a polymer that can form a nanocrystal precursor is added at one time and ultrasonic pulverization is maintained for a certain time to complete the preparation of 4 portions of reverse colloids of loaded matrix nanocrystal precursors with the same formula. Then, the reverse colloid is placed in a microwave generator that can cool and circulate, and microwave irradiated for a certain time at a set power, set frequency and set temperature to obtain 4 portions of microwave-ripened reverse colloids containing aggregated matrix nanocrystal precursors.
[0007] In step (1), the matrix metal salt aqueous solution is one or more of 1% mass concentration water-soluble metal nitric acid, chloride or sulfate formed by iron ions, zinc ions, cadmium ions or chromium ions; the certain polymer aqueous solution is a 1% mass concentration polyethylene glycol (polymer 2000-4000) aqueous solution; the mixed solvent is an oily solvent formed by ether and carbon tetrachloride in a certain ratio; the alkaline polymer aqueous solution is a 1% mass concentration aqueous solution of sodium polyacrylate with a pH value greater than 7.
[0008] In step (1), the mass ratio of the metal salt aqueous solution, the polyethylene glycol aqueous solution, the ether, the carbon tetrachloride and the alkaline polymer aqueous solution is 0.5-1.0:10:30:70:0.5-1.0.
[0009] In step (1), the aqueous phase and the oil phase are mixed and ultrasonically crushed at room temperature for 2 minutes at a power of 200 W by an ultrasonic pulverizer, and then ultrasonically crushed at room temperature for 2 minutes after adding the alkaline polymer aqueous solution; after ultrasonication, the colloid is placed in a 500 W power 2500 MHz microwave irradiation, and the loaded matrix nanocrystal precursor reverse phase colloid is cooled by 30-40° C. circulating water, and the microwave irradiation time of 4 portions of the loaded matrix nanocrystal precursor reverse phase colloid is 10 minutes, 40 minutes, 80 minutes and 120 minutes respectively.
[0010] (2) Preparation of reverse colloids containing doped aggregated matrix nanocrystal precursors with different matching conditions
[0011] Under room temperature conditions, a quantitative amount of doped metal aqueous solution is added to the reverse phase colloid containing matrix nanocrystal precursor with different maturation times in the quantitative step (1), and a quantitative amount of specific auxiliary deposition organic acid is used in combination. After being mixed evenly, each is subjected to ultrasonic crushing for a certain period of time to complete the preparation of several reverse phase colloids containing doped aggregated matrix nanocrystal precursor with different coordination conditions.
[0012] In step (2), the doped metal aqueous solution is one or more of water-soluble rare earth salts such as samarium nitrate, europium nitrate, yttrium nitrate or strontium nitrate with a mass concentration of 0.1%-0.2%; the auxiliary deposition organic acid is formic acid, citric acid, acetic acid or propionic acid; the order of the colloid aging time under microwave irradiation is: colloid with aging time of 120 minutes (with formic acid), colloid with aging time of 80 minutes (with citric acid), colloid with aging time of 40 minutes (with acetic acid) and colloid with aging time of 10 minutes (with propionic acid); or the colloid with aging time of 120 minutes (with propionic acid), colloid with aging time of 80 minutes (with acetic acid), colloid with aging time of 40 minutes (with citric acid) and colloid with aging time of 10 minutes (with formic acid) are prepared in reverse order, thereby completing the preparation of reverse colloids containing doped aggregation matrix nanocrystal precursors with four different aging conditions.
[0013] In step (1), the mass ratio of the reverse phase colloid, the doped metal aqueous solution and the auxiliary deposition acid is 100:0.1:0.1. The ultrasonic pulverizer is ultrasonically pulverized at room temperature for 30 seconds at a power of 200 W.
[0014] (3) Preparation of ordered concentration-doped nanocrystalline coatings
[0015] At room temperature, the reverse phase colloids with different matching conditions prepared in step (2) are mixed evenly in proportion and then spin-coated on a clean conductive quartz glass sheet and naturally air-dried, and then placed in a program-controlled temperature sintering furnace to heat and sinter for a certain period of time. After sintering, cooling is completed to obtain an ordered concentration-doped nanocrystalline coating.
[0016] In step (3), the reverse colloids prepared in step (2) with different matching conditions are mixed in equal mass ratio; the spin coating thickness is 1-2 microns. The program controls the temperature and fixed time as follows: first, the temperature is raised to 150°C, and the retention time is 3 hours; then the temperature is further raised to 200°C, and the retention time is 2 hours; then the temperature is further raised to 250°C and the drying time is 1 hour; then the temperature is raised to 300°C and the drying time is 0.5 hours; finally, the sintering temperature is 500-600°C, and the time is 4-6 hours.
[0017] The invention realizes the preparation of ordered concentration-doped nanocrystalline coatings through an inverse colloidal dispersion system. The coatings prepared by this method have potential application prospects in the fields of optoelectronic materials and high-efficiency catalysts.
[0018] The present invention has the following advantages:
[0019] 1. The matrix nanocrystal precursor contained in the reverse colloid can be subjected to Ostwald ripening by microwave irradiation to obtain an aggregated nanocrystal precursor with a particle size of about 5-10 nanometers;
[0020] 2. By using organic acids with different decomposition temperatures and high-temperature resistant water-based polymers, a reverse colloid containing nanocrystal precursors with different particle sizes was prepared. An ordered concentration-doped nanocrystal coating can be obtained by a single temperature program. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the cross section of the ordered concentration-doped nanocrystalline coating of Example 1 (——20 nanometers) DETAILED DESCRIPTION
[0022] The present invention will be further described in detail below in conjunction with the embodiments.
[0023] Example 1
[0024] (1) Preparation of reverse colloid containing matrix nanocrystal precursor and microwave ripening of the precursor
[0025] At room temperature, 0.3 g of 1% mass concentration iron nitrate aqueous solution, 0.2 g of 1% mass concentration cadmium nitrate aqueous solution and 10 g of 1% mass concentration polyethylene glycol (polymerization degree 2000) aqueous solution were mixed to form an aqueous phase; 30 g of ether and 70 g of carbon tetrachloride mixed solvent were used to form an oil phase. After the aqueous phase and the oil phase were mixed, they were ultrasonically crushed at room temperature for 2 minutes at a power of 200 W, and 0.5 g of 1% mass concentration sodium polyacrylate aqueous solution with a pH of 9 was added and then ultrasonicated at room temperature for 2 minutes to complete the preparation of 4 portions of the reverse colloid of the loaded matrix nanocrystal precursor of the same formula.
[0026] Then, the reverse colloid is placed in a microwave generator capable of cooling and circulation, and the colloid after ultrasonic treatment is placed in a 500W power 2500MHz microwave irradiation, and the reverse colloid loaded with matrix nanocrystal precursor is cooled by 40°C circulating water, wherein the microwave irradiation time of 4 portions of reverse colloid is 10 minutes, 40 minutes, 80 minutes and 120 minutes respectively, and 4 portions of microwave-cured reverse colloid containing aggregated matrix nanocrystal precursor are obtained. The particle sizes of the 4 portions of microwave-cured reverse colloid containing aggregated matrix nanocrystal precursor whose microwave irradiation time is 10 minutes, 40 minutes, 80 minutes and 120 minutes respectively are: 2 nanometers, 4 nanometers, 8 nanometers and 12 nanometers.
[0027] (2) Preparation of reverse colloids with different doped aggregate matrix nanocrystal precursors
[0028] Under room temperature, 0.1 g of 0.1% europium nitrate aqueous solution was added to 100 g of the reverse colloid containing the matrix nanocrystal precursor with aging time of 10 minutes, 40 minutes, 80 minutes and 120 minutes in step (1), respectively, and 0.1 g of formic acid, citric acid, acetic acid or propionic acid was used in combination (specifically: colloid with aging time of 10 minutes + formic acid; colloid with aging time of 40 minutes + citric acid; colloid with aging time of 80 minutes + acetic acid and colloid with aging time of 120 minutes + propionic acid), and then mixed evenly and then ultrasonically crushed for a certain time, and the ultrasonic crusher was ultrasonically crushed for 30 seconds at room temperature with a power of 200 W. The preparation of reverse colloids containing doped aggregated matrix nanocrystal precursors with different combinations was completed.
[0029] (3) Preparation of ordered concentration-doped nanocrystalline coatings
[0030] At room temperature, 4 portions of reverse colloids prepared in step (2) with different coordination conditions are mixed at 20 g: 20 g: 20 g: 20 g, then evenly spin-coated on a clean conductive quartz glass sheet and naturally air-dried to obtain a spin-coated coating with a thickness of 1 micron; then placed in a sintering furnace with program-controlled temperature, and the program-controlled temperature and fixed time are: first heated to 150°C and retained for 3 hours; then heated to 200°C and retained for 2 hours; then heated to 250°C and dried for 1 hour; then heated to 300°C and dried for 0.5 hours; finally sintered at 600°C for 4 hours. After sintering, cool down to obtain an ordered concentration-doped nanocrystalline coating. The coating thickness is 100 nanometers, and the cross-section is as follows: Figure 1 As shown, the europium atomic content from inside to outside is: 1% (0-15 nanometers), 2% (15-35 nanometers), 3% (35-60 nanometers) and 5% (60-100 nanometers).
[0031] Example 2
[0032] (1) Preparation of reverse colloid containing matrix nanocrystal precursor and microwave ripening of the precursor
[0033] At room temperature, 0.6 g of 1% mass concentration iron nitrate aqueous solution, 0.4 g of 1% mass concentration zinc nitrate aqueous solution and 10 g of 1% mass concentration polyethylene glycol (polymerization degree 4000) aqueous solution were mixed to form an aqueous phase; 30 g of ether and 70 g of carbon tetrachloride mixed solvent formed an oil phase. After the aqueous phase and the oil phase were mixed, they were ultrasonically crushed at room temperature for 2 minutes at a power of 200 W, and 1.0 g of 1% mass concentration sodium polyacrylate aqueous solution with a pH of 8 was added and then ultrasonicated at room temperature for 2 minutes to complete the preparation of 4 portions of the reverse phase colloid of the loaded matrix nanocrystal precursor of the same formula.
[0034] Then, the reverse colloid is placed in a microwave generator capable of cooling and circulation, and irradiated with 500W power 2500MHz microwaves, and the reverse colloid of the loaded matrix nanocrystal precursor is cooled by 30°C circulating water, wherein the microwave irradiation time of the four reverse colloids is 10 minutes, 40 minutes, 80 minutes and 120 minutes respectively, and four microwave-ripened reverse colloids containing aggregated matrix nanocrystal precursors are obtained. The particle sizes of the four reverse colloids containing aggregated matrix nanocrystal precursors are 4 nanometers, 10 nanometers, 15 nanometers and 20 nanometers according to the aging time from short to long.
[0035] (2) Preparation of reverse colloids with different doped aggregate matrix nanocrystal precursors
[0036] Under room temperature, 0.1 g of 0.2% samarium nitrate aqueous solution was added to 100 g of the reversed colloid containing the matrix nanocrystal precursor with aging time of 10 minutes, 40 minutes, 80 minutes and 120 minutes in step (1), respectively, and 0.1 g of formic acid, citric acid, acetic acid or propionic acid was used in combination (specifically: colloid with aging time of 120 minutes + formic acid; colloid with aging time of 80 minutes + citric acid; colloid with aging time of 40 minutes + acetic acid and colloid with aging time of 10 minutes + propionic acid), and then mixed evenly and then ultrasonically crushed for a certain time, and the ultrasonic crusher was ultrasonically crushed for 30 seconds at room temperature with a power of 200 W. The preparation of reversed colloid containing doped aggregated matrix nanocrystal precursor with four different combinations was completed.
[0037] (3) Preparation of ordered concentration-doped nanocrystalline coatings
[0038] At room temperature, 4 portions of the reverse phase colloids prepared in step (2) with different matching conditions are mixed evenly at 30 g: 30 g: 30 g: 30 g, and then spin-coated on a clean conductive quartz glass sheet and dried naturally to obtain a spin-coated coating with a thickness of 2 microns; then placed in a program-controlled temperature sintering furnace, the program-controlled temperature and fixed time are: first heated to 150°C, the retention time is 3 hours; then heated to 200°C, the retention time is 2 hours; then heated to 250°C and dried for 1 hour; then heated to 300°C and dried for 0.5 hours; finally sintered at 500°C for 6 hours. After sintering, cool down to obtain an ordered concentration-doped nanocrystalline coating. The coating thickness is 200 nanometers, and the content of samarium atoms in the cross section is from inside to outside: 6% (0-50 nanometers), 4% (50-80 nanometers), 3% (80-130 nanometers) and 2% (130-200 nanometers).
[0039] Example 3
[0040] (1) Preparation of reverse colloid containing matrix nanocrystal precursor and microwave ripening of precursor
[0041] At room temperature, 0.5 g of 1% mass concentration chromium sulfate aqueous solution, 0.3 g of 1% mass concentration zinc chloride aqueous solution and 10 g of 1% mass concentration polyethylene glycol (polymerization degree 3000) aqueous solution were mixed to form an aqueous phase; 30 g of ether and 70 g of carbon tetrachloride mixed solvent formed an oil phase. After the aqueous phase and the oil phase were mixed, they were ultrasonically crushed at room temperature for 2 minutes at a power of 200 W, and 0.8 g of 1% mass concentration sodium polyacrylate aqueous solution with a pH of 8 was added and then ultrasonicated at room temperature for 2 minutes to complete the preparation of 4 portions of the reverse colloid of the loaded matrix nanocrystal precursor of the same formula.
[0042] Then, the reverse colloid is placed in a microwave generator capable of cooling and circulation, and irradiated with 500W power 2500MHz microwaves, and the reverse colloid of the loaded matrix nanocrystal precursor is cooled by 35°C circulating water, wherein the microwave irradiation time of the four reverse colloids is 10 minutes, 40 minutes, 80 minutes and 120 minutes respectively, and four microwave-ripened reverse colloids containing aggregated matrix nanocrystal precursors are obtained. The particle sizes of the four reverse colloids containing aggregated matrix nanocrystal precursors are 3 nanometers, 6 nanometers, 10 nanometers and 16 nanometers according to the aging time from short to long.
[0043] (2) Preparation of reverse colloids with different doped aggregate matrix nanocrystal precursors
[0044] Under room temperature, 0.1 g of 0.1% yttrium nitrate aqueous solution was added to 100 g of the reverse phase colloid containing the matrix nanocrystal precursor with aging time of 10 minutes, 40 minutes, 80 minutes and 120 minutes in step (1), respectively, and 0.1 g of formic acid, citric acid, acetic acid or propionic acid was used in combination (specifically: colloid with aging time of 10 minutes + formic acid; colloid with aging time of 40 minutes + citric acid; colloid with aging time of 80 minutes + acetic acid and colloid with aging time of 120 minutes + propionic acid), and then mixed evenly and then ultrasonically crushed for a certain time, and the ultrasonic crusher was ultrasonically crushed for 30 seconds at room temperature with a power of 200 W. The preparation of reverse phase colloids containing doped aggregated matrix nanocrystal precursors with different combinations was completed.
[0045] (3) Preparation of ordered concentration-doped nanocrystalline coatings
[0046] At room temperature, 4 portions of the reverse phase colloids prepared in step (2) with different matching conditions are mixed at 25 g: 25 g: 25 g: 25 g, and then spin-coated on a clean conductive quartz glass sheet and dried naturally to obtain a spin-coated coating with a thickness of 1.5 microns; then placed in a sintering furnace with program-controlled temperature, and the program-controlled temperature and fixed time are: first heated to 150°C, and the retention time is 3 hours; then heated to 200°C, and the retention time is 2 hours; then heated to 250°C and dried for 1 hour; then heated to 300°C and dried for 0.5 hours; finally sintered at 550°C for 5 hours. After sintering, cool down to obtain an ordered concentration-doped nanocrystalline coating. The coating thickness is 150 nanometers, and the yttrium atomic content of the cross section is from inside to outside: 2% (0-20 nanometers), 4% (20-50 nanometers), 5% (50-90 nanometers) and 7% (90-150 nanometers).
[0047] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and modifications made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing an ordered concentration-doped nanocrystalline coating by an inverse colloidal dispersion system, characterized in that: The method steps are as follows: (1) Preparation of reverse colloid containing matrix nanocrystal precursor and microwave ripening of the precursor At room temperature, a matrix metal salt aqueous solution and a polymer aqueous solution are mixed to form an aqueous phase; a mixed solvent forms an oil phase; after the oil and water phases are mixed, they are transferred to an ultrasonic pulverizer for pulverization, and then an alkaline aqueous solution of a polymer that can form a nanocrystal precursor is added at one time and then ultrasonic pulverization is maintained to complete the preparation of 4 portions of reverse colloids loaded with matrix nanocrystal precursors; then, the reverse colloids are placed in a microwave generator that can cool and circulate and microwave irradiated separately to obtain 4 portions of reverse colloids containing aggregated matrix nanocrystal precursors with different microwave ripening times; (2) Preparation of reverse colloids with different doped aggregate matrix nanocrystal precursors Under room temperature, adding a doped metal aqueous solution and an auxiliary deposition organic acid to four portions of the matrix-containing nanocrystal precursor reverse colloids having different maturation times in step (1), respectively, mixing them evenly and then ultrasonically crushing them respectively, to complete the preparation of four portions of doped aggregate matrix-containing nanocrystal precursor reverse colloids having different matching conditions; (3) Preparation of ordered concentration-doped nanocrystalline coatings At room temperature, the four portions of reverse colloids with different matching conditions prepared in step (2) are mixed evenly in proportion and then spin-coated on a clean conductive quartz glass sheet and naturally air-dried. The mixture is placed in a program-controlled temperature sintering furnace to heat and sinter. After sintering, the mixture is cooled to obtain an ordered concentration-doped nanocrystalline coating.
2. The method for preparing an ordered concentration-doped nanocrystalline coating by an inverse colloidal dispersion system according to claim 1, characterized in that: In step (1), the matrix metal salt aqueous solution is a 1% mass concentration aqueous solution formed by one or more of metal nitric acid, chloride or sulfate of iron ion, zinc ion, cadmium ion or chromium ion; the polymer aqueous solution is a 1% mass concentration polyethylene glycol aqueous solution; the mixed solvent is a mixed oily solvent of ether and carbon tetrachloride; the alkaline polymer aqueous solution is a 1% mass concentration aqueous solution of sodium polyacrylate with a pH value greater than 7.
3. The method for preparing an ordered concentration-doped nanocrystalline coating by an inverse colloidal dispersion system according to claim 1, characterized in that: In step (1), the mass ratio of the metal salt aqueous solution, the polyethylene glycol aqueous solution, the ether, the carbon tetrachloride and the alkaline polymer aqueous solution is 0.5-1.0:10:30:70:0.5-1.
0.
4. The method for preparing an ordered concentration-doped nanocrystalline coating by an inverse colloidal dispersion system according to claim 1, characterized in that: In step (1), the aqueous phase and the oil phase are mixed and ultrasonically crushed at room temperature for 2 minutes at a power of 200 W by an ultrasonic pulverizer, and then ultrasonically crushed at room temperature for 2 minutes after adding the alkaline polymer aqueous solution; after ultrasonication, the colloid is placed in a 500 W power 2500 MHz microwave irradiation, and the loaded matrix nanocrystal precursor reverse phase colloid is cooled by 30-40° C. circulating water, and the microwave irradiation time of 4 portions of the loaded matrix nanocrystal precursor reverse phase colloid is 10 minutes, 40 minutes, 80 minutes and 120 minutes respectively.
5. The method for preparing an ordered concentration-doped nanocrystalline coating by using an inverse colloidal dispersion system according to claim 1, characterized in that: In step (2), the doped metal aqueous solution is an aqueous solution of one or more of samarium nitrate, europium nitrate, yttrium nitrate or strontium nitrate water-soluble rare earth salts with a mass concentration of 0.1-0.2%; the auxiliary deposition organic acid is formic acid, citric acid, acetic acid or propionic acid; wherein the organic acids prepared in order of microwave irradiation colloid maturation time are: formic acid prepared in order of maturation time of 120 minutes, citric acid prepared in order of maturation time of 80 minutes, acetic acid prepared in order of maturation time of 40 minutes, and propionic acid prepared in order of maturation time of 10 minutes; or the organic acids prepared in reverse order are: propionic acid prepared in order of maturation time of 120 minutes, acetic acid prepared in order of maturation time of 80 minutes, citric acid prepared in order of maturation time of 40 minutes, and formic acid prepared in order of maturation time of 10 minutes.
6. The method for preparing an ordered concentration-doped nanocrystalline coating by an inverse colloidal dispersion system according to claim 1, characterized in that: In step (2), the mass ratio of the reverse phase colloid, the doped metal aqueous solution and the auxiliary deposition organic acid in step (1) is 100:0.1:0.1, and the ultrasonic pulverizer is ultrasonically pulverized at room temperature for 30 seconds at a power of 200 W.
7. The method for preparing an ordered concentration-doped nanocrystalline coating by using an inverse colloidal dispersion system according to claim 1, characterized in that: In step (3), the reverse phase colloids with different matching conditions prepared in step (2) are mixed in equal mass ratio; and the spin coating thickness is 1-2 microns.
8. The method for preparing an ordered concentration-doped nanocrystalline coating by using an inverse colloidal dispersion system according to claim 1, characterized in that: In step (3), the program controls the temperature and fixed time as follows: first, heat to 150°C and keep it for 3 hours; then heat to 200°C and keep it for 2 hours; then heat to 250°C and dry it for 1 hour; then heat to 300°C and dry it for 0.5 hour; finally, the sintering temperature is 500-600°C and the time is 4-6 hours.
9. An ordered concentration-doped nanocrystalline coating prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A method of avoiding generation of cracks in a colloidal crystal preparation process
CN104607117A
Waterborne polyurethane Pickering emulsion and preparation method thereof
CN116178934A
Method for preparing doped nanocrystals by using amino polymer reversed-phase miniemulsion colloid
CN116924477A
Method for doping nanocrystalline on surface of polymer coating by using Pickering miniemulsion
CN118406409A